2022
DOI: 10.3389/fpubh.2021.804626
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-Related Knowledge and Attitudes Among Chinese College Students and Associated Factors: A Cross-Sectional Study

Abstract: In recent years, adolescent has become one of the high-risk groups for HIV. Meanwhile, good HIV awareness and positive attitude are essential for HIV prevention. This study aims to evaluate the extent to which college students understand HIV and their attitudes toward HIV-infected patients, as well as the correlative factors. The data used in this study came from a cross-sectional survey. An anonymous online questionnaire was used to investigate the demographic characteristics, HIV/AIDS-related knowledge, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
2
17
3
2
Order By: Relevance
“…This reflects the factors such as students' cultural literacy, sexual education investment, and attention in school have a positive significance in prevention of AIDS. In this study, the awareness rate of AIDS did not differ by gender, schools, whether they are or not only child, parent education level, family monthly income, and residence style, this finding conflicts with some earlier researches ( 30 , 31 ). Future studies may wish to assess a wider range of influence factors to better understand which affects the awareness rate of AIDS.…”
Section: Discussioncontrasting
confidence: 99%
“…This reflects the factors such as students' cultural literacy, sexual education investment, and attention in school have a positive significance in prevention of AIDS. In this study, the awareness rate of AIDS did not differ by gender, schools, whether they are or not only child, parent education level, family monthly income, and residence style, this finding conflicts with some earlier researches ( 30 , 31 ). Future studies may wish to assess a wider range of influence factors to better understand which affects the awareness rate of AIDS.…”
Section: Discussioncontrasting
confidence: 99%
“…A lack of sexual knowledge leads to not only an increased infection rate of HIV/AIDS (7) but also other reproductive…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that most participants demonstrated their basic knowledge of the primary transmission modes of HIV, which confirmed the existing findings about Chinese college students' HIV/AIDS knowledge. [33][34][35] However, the participants seldom continued to tell more details about their knowledge of HIV/AIDS, especially high-risk sexual conducts of AIDS. Similar findings were obtained in prior investigations 1,36 which reported that Chinese students who majored in medicine displayed richer knowledge on the HIV/AIDS than those who majored in humanities and social sciences.…”
Section: Discussionmentioning
confidence: 99%